1999
DOI: 10.1021/la981103m
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Activity Studies of Vanadia Supported on Zirconia and Phosphorus-Modified Zirconia

Abstract: A series of catalysts with vanadia contents varying between 1 and 14 wt % were prepared by the wet impregnation technique on zirconia and phosphorus-modified zirconia. The catalysts were characterized by employing X-ray diffraction (XRD), electron spin resonance (ESR) spectroscopy, 51V, 31P, and 1H solid-state magic angle spinning nuclear magnetic resonance (MAS NMR), Fourier transform Raman spectroscopy (FT-Raman), diffuse reflectance Fourier transform infrared spectroscopy (DRIFTS), and Brunauer−Emmett−Telle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…The molecular structure of these supported vanadium oxide species has been studied by a wide variety of spectroscopic techniques, including Raman, 51 V NMR, UV-vis-near-infrared, extended X-ray absorption fine structure (EXAFS), X-ray absorption near-edge spectroscopy, electron spin resonance, and X-ray photoelectron spectroscopy. [5][6][7][8][9][10][11][12][13][14][15][16][17][18] Several review papers, which describe the current understanding of these catalytic systems, [18][19][20][21] can be found in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…The molecular structure of these supported vanadium oxide species has been studied by a wide variety of spectroscopic techniques, including Raman, 51 V NMR, UV-vis-near-infrared, extended X-ray absorption fine structure (EXAFS), X-ray absorption near-edge spectroscopy, electron spin resonance, and X-ray photoelectron spectroscopy. [5][6][7][8][9][10][11][12][13][14][15][16][17][18] Several review papers, which describe the current understanding of these catalytic systems, [18][19][20][21] can be found in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Vanadium based catalysts belong to the most investigated and promising catalytic systems for the ODH of ethanol. Previous studies demonstrated that catalytic activity of the catalyst depend on nature of the support and speciation of vanadium complexes [50][51][52][53][54]. Regarding the activity and selectivity pair of parameters, the tetrahedral oligomeric vanadate species seems to be the most appropriate catalytic entities [50,52,55,56].…”
Section: Introductionmentioning
confidence: 97%
“…Vanadium oxides are widely used as catalysts in oxidation reactions, for example, the oxidation of sulfur dioxide, carbon monoxide, and hydrocarbons. These systems have also been found to be effective catalysts for the oxidation of methanol to methylformate , and for the selective catalytic reduction of nitrogen oxide. , Much research has been done to understand the nature of active sites, the surface structure of catalysts, and the role played by the promoter of the supported catalysts, using infrared (IR), X-ray diffraction (XRD), electron spin resonance (ESR), and Raman spectroscopy. , So far, silica, titania, zirconia, and alumina have been commonly employed as the vanadium oxide supports.…”
Section: Introductionmentioning
confidence: 99%